Radical cystectomy: Analysis of postoperative course - Jeremić Dimitrije; Vojinov Saša; Marušić Goran; Levakov Ivan; Živojinov Srđan (Vojnosanitetski Pregled)
Background/Aim. Radical cystectomy is a method of choice in the therapy of infiltrative bladder cancer. The aim of this research was to analyze postoperative course after radical cystectomy (length of hospitalization, most frequent complications and utilization of antibiotics and transfusions). Methods. We analyzed the records of 82 patients operated on in the Department of Urology, Clinical Center of Vojvodina, in a three-year period. In order to aquire data World Health Organization (WHO) has developed Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) methodology. Defined daily dose (DDD) is the assumed average maintenance dose per day for a drug use for its main indication. Results. Continent urinary derivation was preformed in 23.15% cases. Postoperative complications occurred in 18.29% of patients. Average blood utilization was 2.19 units. Blood utilization for continent derivations (n = 48) was 4.6 units, and incontinent ones 3.36 units. Totally 159.33 DDD/100 bed days were used. Conclusion. When preforming continent derivation there is a significant increase in blood utilization. Frequency of postoperative complications correlates to those reported in the literature.